Coolhouse.id Business Success Analysis - Ferly Festyana (International Journal of Applied Business and International Management, 2022)
Knowledge of entrepreneurship is essential for business people who want to start or develop their business ventures. This study aims to analyze the success of Coolhouse.id's business in terms of internal factors, namely the entrepreneurial characteristics of the owner. This study used a qualitative approach with case study research. The data was collected using observation techniques, interviews, and documentation. The analysis results show that the characteristics of entrepreneurs have a significant role in the success of Coolhouse.id's business. Creative and innovative factors are the most important because they enable entrepreneurs to make products or ways that are different from other competitors allowing their originality attracts consumers and customers.